(untitled) (Conferencea, 2023)
This research paper examines current problems related to cost optimization in the vocational education system of Uzbekistan and presents potential solutions to these problems. Moreover, it examines such factors as resource allocation, curriculum development, technology integration, and strategic collaboration to achieve effective academic process.